Obstetric risk factors for poor neonatal adaptation at birth. (17th September 2018) - Crovetto, Francesca; Fumagalli, Monica; De Carli, Agnese; Baffero, Giulia Maria; Nozza, Silvia; Dessimone, Francesca; Vergani, Patrizia; Fedele, Luigi; Mosca, Fabio; Acaia, Barbara
Abstract: Purpose: To identify obstetric risk factors of delivering a neonate with poor neonatal adaptation at birth. Material and methods: Nested case–control study. Poor neonatal adaptation was defined for presence of at least: umbilical cord artery pH <7.10, base deficit ≥12 mmol/L, Apgar score at 1′ ≤5. Controls were selected from the same population and matched with cases. The association between clinical parameters and poor neonatal adaptation was analyzed by logistic regression. Results: One hundred and thirty three women (2.1% of all live births) with a neonate presenting a poor neonatal adaptation were matched with 133 subsequent controls. Significant contributions for the prediction of poor neonatal adaptation were provided by maternal age ≥35 years ( p ≤ .001, odds ratio (OR) 3.9 [95%CI: 2.3–6.8]), nulliparity ( p ≤ .001, OR 3.3 [95%CI: 1.8–6]), complications during pregnancy ( p = .032, OR 2.2 [95%CI: 1.1–4.4]), gestational age at delivery <37 weeks ( p = .008, OR 5.2 [95%CI: 1.5–17.8]) and cardiotocography category II or III ( p ≤ .001, OR 36.3 [95%CI: 16.5–80.1]). The receiver operative characteristic curve was 0.91 [95%CI: 0.87–0.95], and detection rates 82.7% and 89.5% at 10% and 20% of false positive rates, respectively. Conclusions: Several obstetric risk factors before and during labor can identify a subgroup of newborns at higher risk of a poor neonatal adaptation at birth.